A systematic review of ego depletion phenomenon in group-based hierarchical relations - Genç Turhan, Funda; Kuşdil, Muharrem Ersin (Frontiers in Psychology, 2025)
IntroductionThis systematic review examines the relationship between intergroup relations and ego depletion, aiming to understand how self-control resources are affected in social hierarchies.MethodsA total of 35 peer-reviewed articles and four unpublished doctoral dissertations were reviewed. Findings were categorized based on the social position of the target person’s group in intergroup interactions.ResultsIntergroup contacts depleted the self-control resources of dominant group members when they were required to suppress biases. For subordinate group members, engaging in intergroup interactions, witnessing bias, or facing bias threats also depleted self-control resources. Depleted dominant members exhibited increased prejudice and stereotyping, whereas depleted subordinate members showed lower perception of prejudiced behaviors and higher liking for dominant group members.DiscussionThe findings are interpreted within the framework of social dominance theory, highlighting how ego depletion influences intergroup relations and reinforcing the role of group-based hierarchies in shaping social behavior.